2006
DOI: 10.1007/s00535-006-1801-6
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer: genetics of development and metastasis

Abstract: It has been well documented that there are two major pathways in colorectal carcinogenesis. One is the chromosomal instability pathway (adenoma-carcinoma sequence), which is characterized by allelic losses on chromosome 5q (APC), 17p (p53), and 18q (DCC/SMAD4), and the other is a pathway that involves microsatellite instability. Recent progress in molecular biology, however, has shown that colorectal carcinogenesis is not necessarily clearly divided into these two pathways, but is in fact more complicated. Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
139
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(148 citation statements)
references
References 84 publications
8
139
0
Order By: Relevance
“…Metastasis to the liver is the major cause of death in CRC patients (3). The formation of liver metastases is a multistep process involving the escape of tumor cells from a primary CRC, intravasation into the systemic circulation, survival during transit in the vasculature, extravasation into the parenchyma of liver tissues, and ultimately the outgrowth of macroscopic liver metastasis formation through proliferation and angiogenesis (4)(5)(6). Although research has identified multiple genes responsible for liver metastasis (7), the epigenetic alterations that drive metastasis to the liver are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis to the liver is the major cause of death in CRC patients (3). The formation of liver metastases is a multistep process involving the escape of tumor cells from a primary CRC, intravasation into the systemic circulation, survival during transit in the vasculature, extravasation into the parenchyma of liver tissues, and ultimately the outgrowth of macroscopic liver metastasis formation through proliferation and angiogenesis (4)(5)(6). Although research has identified multiple genes responsible for liver metastasis (7), the epigenetic alterations that drive metastasis to the liver are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There was a clue that TIMP3 may exhibit pro-apoptotic properties in corneal stromal cells. 1 We detected whether Ad-TIMP3 works on colon cancer cells through inducing apoptosis. From Figure 2b, poly ADP-ribose polymerase (PARP) cleavage was increasingly obvious in Ad-TIMP3-treated cells, which indicated that TIMP3 transfer induced apoptosis of CT26 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Many genes have been identified as being involved in migration, adhesion and angiogenesis steps of metastasis process, such as APC, p53 and DCC/SMAD4. 1 Tissue inhibitor of metalloproteinases (TIMPs) are the proteins to anti-act the matrix metalloproteinase (MMP) activity, keeping the balance of TIMPs and MMPs. Among the TIMPs, TIMP3 is demonstrated to be associated with powerful anticancer capacity.…”
Section: Introductionmentioning
confidence: 99%
“…FGF1 is a pleiotropic growth factor known to regulate proliferation, migration, and differentiation of target cells, and it has been shown to promote intestinal epithelial cell migration. 17 A recent article has additionally shown that overexpression of FGFR correlates with liver metastasis in CRC, 18 and the splice form IIIc of FGFR3 has been suggested to have oncogenic effect on CRC cells. 19 Because both a block of FGFR and use of a neutralizing FGF1 antibody attenuated cancer cell migration in our assay, we speculate that FGF signaling might be one pathway responsible for the low clinical efficiency seen when using the FAP-inhibitor talabostat on metastatic CRC patients.…”
Section: Discussionmentioning
confidence: 99%